The Mushroom-Rimmed Amphora as an Indicator of Hekatomnid Regional Hegemony: An Analysis of Production Patterns Based on a Back-Filled Deposit at Patara - Dündar, Erkan (Jahrbuch des Deutschen Archäologischen Instituts, 2022)
The excavations on the Tepecik settlement at Patara furnish important new evidence for the mushroom-rimmed amphorae in the 4th c. B.C. This evidence is based primarily on the ceramics recovered from a back-filled burnt soil layer in a deposit located on the Tepecik settlement. These finds include eight amphorae and two unguentaria. One of these amphorae is Lycian, and seven others belong to the mushroom-rimmed amphora type. Our analysis indicates that the mushroom-rimmed amphora reflects production and distribution of commodities generated under the aegis of the Hecatomnid dynasty in Karia and the mushroom rim could have been used as a geographical marker, a ›brand‹ by the Hekatomnids during the 4th c. B.C.